REFORMASI ADMINISTRASI MENUJU PUBLIC SERVICE DALAM SEKTOR PENDIDIKAN, KESEHATAN, DAN EKONOMI MASYARAKAT PADA PEMERINTAH DAERAH - Adriani Adnani (Ensiklopedia Social Review, 2021)
The role and character of state institutions and the public sector are more directed to be oriented towards the community. This condition initially occurred in various developed countries, which then spread to developing countries. Of course, many factors caused this to happen, such as the economic and financial crisis of the state. Public administration reform towards public service is important enough to get attention and treatment as soon as possible. The dynamics of society as a social force cannot be ignored in the system of control and public accountability, both in service delivery and in the implementation of development. The purpose of this study is to find out the New Public Service paradigm as a new concept in administrative reform in the education, health and economic sectors of the local government. The results of the study indicate that public services in the education, health, and economic sectors of today's society are facing a trend towards the development of regional governance as a result of globalization and regional autonomy. In the management of local government, a change and renewal is needed so that the government can always accommodate the needs of change in society and enable public administration to reorganize people's lives. One of the trends in the need for public bureaucracy to reform is that local government bureaucracies must be more open in relation to the public interest. In other words, the local government bureaucracy can become more flexible so that it can more easily adapt to changing circumstances. With the administrative reform towards public service, it is hoped that it can encourage the realization of good governance, improve performance and improve unhealthy administrative practices.